UPACARA PITRA YADNYA DI BAJAR SUKA WARDAYA DI TENGAH PUSARAN PERUBAHAN MASYARAKAT SAAT INI - Ni Kadek Whida Gandeswari; I Ketut Sumada (Widya Sandhi, 2021)
This paper is the result of research that aims to analyze the adaptation of the Pitra Yadnya or Ngaben ceremony carried out by the Hindu community in Banjar Suka Wardaya, Babakan Village, Gerung District, West Lombok Regency. This study uses a qualitative descriptive method. The form of adaptation in the implementation of the pitra yadnya ceremony in the Hindu community in the location of research is indicated by a change in the implementation of the pitra yadnya ceremony which previously emphasized the family aspect to become the mass of pitra yadnya ceremony. The implementation of cremation carried out in the family is only assisted by certain people who are related to their family or related to their sidhikara. After the Pitra Yadnya ceremony was held, the community of banjar helped with the ceremonial activities and several sawa (corpses) could be held for the Pitra yadnya ceremony simultaneously. Second, the adaptation process in the implementation of the pitra yadnya ceremony in general goes through three stages. (1) there is an idea from Hindu leaders to carry out the pitra yadnya ceremony en masse. (2) implementing these ideas into concrete actions so that they take the form of mass cremation activities. (3) the continuation of the mass pitra yadnya ceremony because it has benefits for the Hindu community in Banjar Suka Wardaya. Third, there are four meanings of adaptation in the implementation of the pitra yadnya ceremony in Babakan Village. (1) the economic meaning is related to cost reduction. (2) social meaning is related to strengthening social relations between citizens. (3) religious meaning is related to carrying out obligations in accordance with religious teachings. (4) the meaning of education is to increase knowledge in making facilities for the Ngaben ceremony.